From Struggle to Fluency: Teacher Solutions to Quranic Reading Barriers in Senior High School - Zurmalia, Arini; Fitri, Rika; Ernayenti, Ernayenti (Al-kayyis: Journal of Islamic Education, 2025)
Students' difficulties in reading the Quran are a significant challenge in Islamic Religious Education at the high school level. This study aims to identify and analyze teachers' efforts in overcoming these obstacles. This study uses a qualitative approach with a case study design, through data collection techniques such as observation, interviews, and documentation. The main informants are Islamic Religious Education teachers, supported by the principal and curriculum deputy. The results show that teachers apply three main strategies: i) providing motivation through varied learning methods such as group discussions, demonstrations, and question-and-answer sessions to increase student enthusiasm, ii) providing examples of good Quran reading with the help of teaching aids and digital technology to clarify makhraj and tajwid; and iii) accustoming students to reading the Quran regularly through halaqah methods and youth wirid activities. This strategy has proven effective in improving students' ability to read the Quran, despite challenges such as limited learning time, differences in student backgrounds, and a lack of support from the family environment. The implications of this study indicate that the active role of teachers, the support of school principals, and the involvement of parents are very important in shaping a culture of reading the Quran in the school environment. These findings are expected to serve as a reference for educational institutions in designing more effective and sustainable Quran learning strategies.